Ethylene oligomerization studies by nickel(ii) complexes chelated by (amino)pyridine ligands: experimental and density functional theory studies. Issue 8 (21st January 2016) - Nyamato, George S.; Ojwach, Stephen O.; Akerman, Matthew P.
Abstract : Activation of (amino)pyridine nickel(ii ) complexes1–4 with either EtAlCl2 or methylaluminoxane (MAO), produced active ethylene oligomerization catalysts to afford mostly butenes and hexenes and octenes as minor products. Abstract : Reductions of imine compounds 2-methoxy- N -(1-(pyridin-2-yl)ethylidene)ethanamine (L1 ), 2-methoxy- N -((pyridin-2-yl)methylene)ethanamine (L2 ), N, N -diethyl- N -((pyridin-2-yl)methylene)ethane-1, 2-diamine (L3 ) and 2-((pyridin-2-yl)methyleneamino)ethanol (L4 ) using NABH4 produced their corresponding amine analogues N -(2-methoxyethyl)-1-(pyridin-2-yl)ethanamine (L1a ), 2-methoxy- N -((pyridin-2-yl)methyl)-ethanamine (L2a ), N, N -diethyl- N -((pyridin-2-yl)methyl)ethane-1, 2-diamine (L3a ) and 2-((pyridin-2-yl)methylamino)ethanol (L4a ) in good yields. Reactions of the (amino)pyridine ligandsL1a–L4a with [NiBr2 (DME)] afforded nickel(ii ) complexes, [NiBr2 (L1a )2 ] (1 ), [NiBr2 (L2a )2 ] (2 ), [NiBr2 (L3a )2 ] (3 ) and [NiBr2 (L4a )2 ] (4 ), respectively in quantitative yields. Molecular structures of complexes2 and4 confirmed the formation of the bis(chelated)nickel(ii ) complexes. Activation of complexes1–4 with either EtAlCl2 or methylaluminoxane (MAO), produced active ethylene oligomerization catalysts to afford mostly ethylene dimers (C4 ), in addition to trimmers (C6 ) and tetramers (C8 ). Density functional theory studies provided valuable insight into the reactivity trends and influence of complex structure on the ethylene oligomerization reactions.